Peningkatan Kemampuan Membaca Kata Benda Berpola KV-KV Melalui Penerapan Metode Fernald pada Murid Disabilitas Intelektual Ringan - Tiara Afmita; Zulmiyetri; Nurhastuti; Yosa Yulia Nasri (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The low ability to read nouns with the CV-CV pattern in students with mild intellectual disabilities is the basis for this study. The study aims to describe the improvement in the ability to read nouns with the CV-CV pattern through the application of the Fernald method in a sixth-grade student with mild intellectual disabilities at SLBN 1 Linggo Sari Baganti who has difficulty recognizing and reading simple nouns. The study used an experimental method with a Single Subject Research (SSR) A–B (baseline–intervention) design. Data were collected through tests, observations, and interviews, then analyzed using visual graphic analysis that included analysis within conditions (condition length, directional tendency, stability, level changes, and data traces) as well as analysis between conditions to compare changes between the baseline and intervention phases. The results showed an increase in reading ability, marked by an increase in scores from 20% in the baseline phase to 95% at the end of the intervention phase as well as a change in data trends towards the better. These findings indicate that the application of the Fernald method contributed to the improvement in the ability to read nouns with the CV-CV pattern in the study subjects